ID EFL LEARNING: AN IMPLICATION FOR LEARNING INTERNALIZATION - Saniago Dakhi; Erni Murniarti; Noh Ibrahim Boiliu; Mila Falma Masful (English Review: Journal of English Education, 2019)
It is plausible that the psychoanalysis approach holds an important role in exploring people’s personalities, the world of conscious drives. The human personality is categorized into id, ego, and superego, while consciousness is divided into three different provinces, namely unconscious, subconscious, and conscious. However, language teachers’ interest in exploring such beneficial approach to learning is limited. To respond to such gap, a systematic literature review was employed following phases: identification, comprehension, application, analysis, and synthesis. Results revealed that four id EFL learning characteristics are primitive personality, biological identity, an instinct to seek pleasure, and automaticity. Hiding, covering, and undressing are the indicators of the primitive personality and are human biological responses to danger. On the other hand, the human senses, cognitive process, and speech organs define the EFL learners’ biological personality. As for the automaticity learning, it seems to be achievable by unconscious learning and good learning culture. The basic assumption is that a higher-level skill cannot be acquired unless a lower one has been automatized. Applying such concepts, the characteristics of seeking pleasure to learn language, needs the creativity of EFL teachers, delightful teaching, good teaching culture, and facilities as once EFL learning automatized or internalized, enormous impact will be gained.